PLANT BOTANICALS, A PROMISING FUTURE PESTICIDE FOR BOTH FIELD AND STORE INSECT PESTS: A REVIEW - Samaila, A.; Mubarak, M. U.; Abdulrahman, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The escalating concerns over synthetic pesticide-associated human health hazards, environmental contamination and accelerating insecticide resistance in pest populations have intensified the global search for safer and more sustainable alternatives. Botanical pesticides derived from plant secondary metabolites including alkaloids, terpenoids, flavonoids and essential oils represent a promising class of biopesticides that are biodegradable, locally accessible and generally compatible with integrated pest management (IPM) frameworks. This review examines the current state of knowledge on the efficacy of plant-derived botanical extracts, powders and essential oils for the management of both field crop and stored grain insect pests. Key botanical sources reviewed include neem (Azadirachta indica), pyrethrum (Chrysanthemum cinerariaefolium), garlic (Allium sativum), Mexican sunflower (Tithonia diversifolia), eucalyptus (Eucalyptus globulus), tobacco (Nicotiana tabacum) and Annona (Annona squamosa) among others. Their documented bioactive compounds, mechanisms of pesticidal action and efficacy against major pest species are critically synthesised from recent literature (2020–2025). The review further discusses the comparative advantages and limitations of botanical pesticides relative to synthetic counterparts, challenges to their commercialization, regulatory approval and emerging innovations such as nano-formulations and synergistic multi-plant combinations. It is concluded that botanical pesticides, while not yet a wholesale replacement for synthetic insecticides, constitute an indispensable component of future sustainable pest management systems, particularly for smallholder farming communities in sub-Saharan Africa and other tropical regions. Strategic investment in formulation technology, field validation, and harmonised regulatory frameworks is urgently needed to unlock their full potential.